2012
DOI: 10.1248/bpb.b12-00387
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effects of Telmisartan on the Inflammatory Response and Impaired Spatial Memory in a Rat Model of Alzheimer’s Disease Incorporating Additional Cerebrovascular Disease Factors

Abstract: Telmisartan, an angiotensin type 1 receptor blocker, is used in the management of hypertension to control blood pressure. In addition, telmisartan has a partial agonistic effect on peroxisome proliferator activated receptor γ (PPARγ). Recently, the effects of telmisartan on spatial memory or the inflammatory response were monitored in a mouse model of Alzheimer's disease (AD). However, to date, no studies have investigated the ameliorative effects of telmisartan on impaired spatial memory and the inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 39 publications
(50 reference statements)
0
25
0
Order By: Relevance
“…Recently, many experimental treatments with anti-inflammatory agents were tested in animal models of AD as well, such as: CHF5074, a non-steroidal anti-inflammatory drug [33]; aspirintriggered LXA4 [34]; telmisartan [35]; cyclooxygenase-1 [36]; minocycline [37] and several cannabinoids [5]. They inhibited or modulated microglial activation, attenuated neuroinflammatory reaction, reduced AD-like pathology, some of them also improved cognitive deficits in transgenic mouse models of AD, similar as Oridonin's effect observed in our present study.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many experimental treatments with anti-inflammatory agents were tested in animal models of AD as well, such as: CHF5074, a non-steroidal anti-inflammatory drug [33]; aspirintriggered LXA4 [34]; telmisartan [35]; cyclooxygenase-1 [36]; minocycline [37] and several cannabinoids [5]. They inhibited or modulated microglial activation, attenuated neuroinflammatory reaction, reduced AD-like pathology, some of them also improved cognitive deficits in transgenic mouse models of AD, similar as Oridonin's effect observed in our present study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also showed that, unlike other AT1 receptor antagonists, telmisartan activates PPAR-γ receptors [14,15]. Positive effects of telmisartan on the central nervous system have also been demonstrated [16]. Jaggi and Singh explored the potential of telmisartan in chronic constriction injury-induced neuropathic pain in rats [17].…”
Section: Introductionmentioning
confidence: 99%
“…Aggregated Aβ was prepared as previously described . Aβ42 peptides were purchased from Anaspec (Fremont, CA, USA), dissolved in HEPES‐buffered solution to a final concentration of 10 µmol/L, and incubated at 37°C for 7 days.…”
Section: Methodsmentioning
confidence: 99%
“…The Aβ + CI rats (water maze task, n = 24; eight‐arm radial maze task, n = 38) were prepared by combining intracerebroventricular Aβ injection with transient CI as previously described . Rats were anesthetized with sodium pentobarbital.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation